Compliance with hand hygiene practices among nursing staff in secondary healthcare hospitals in Kuwait - Sarah Al-Anazi; Nora Al-Dhefeery; Rawan Al-Hjaili; Awsaf Al-Duwaihees; Ahad Al-Mutairi; Reem Al-Saeedi; Retaj Al-Dhaen; Sara Al-Rabiah; Reem Sharaf-Alddin (BMC, 2022)
Abstract Background Hand hygiene (HH) among healthcare workers, especially nurses, is the main preventive measure to control healthcare associated infections but compliance with hand hygiene (CwHH) remains low in various settings including Kuwait. This study aimed to assess the knowledge of, attitudes towards, and CwHH among nursing staff in secondary care hospitals in Kuwait. Methods A cross-sectional study was conducted on nursing staff in all six secondary care hospitals in Kuwait. Data on knowledge of, attitudes towards, and self-reported CwHH were collected through a self-administered questionnaire that was developed based on WHO's questionnaire, while the data on actual compliance were objectively collected through direct observation of nurses during routine care by two independent observers using WHO's observation form. Results Of 829 nurses approached, 765 (92.2%) responded and participated. Of all participants, 524 (68.5%) were able to list "My Five Moments for Hand Hygiene" fully and appropriately. However, several misconceptions (e.g. air circulation in hospital is the main route of infection) about HH were found among the nurses. CwHH was (25.0%) by direct observation while self-reported compliance was (69.5%) each varied significantly (p < 0.001) between different hospitals. Female nurses compared to male nurses and non-Arab compared to Arab nationalities were more likely to report CwHH in multivariable analysis. Several items on knowledge of and attitudes towards HH were also associated with self-reported CwHH. Conclusion Observed CwHH among nursing staff in secondary care hospitals in Kuwait was low, which highlights the need to make more efforts to improve HH practices. Interventions that have been used elsewhere and found to be effective may be tested in Kuwait. Despite the good overall knowledge on HH among nurses, there are several misconceptions that need to be corrected.